Selection Criteria in the Search for a Sperm Donor: Internal Versus External Attributes - Benno Torgler; Stephen Whyte (Center for Research in Economics, Management and the Arts (CREMA), 2013)
Despite extensive literature on female mate choice, empirical evidence on women's preferences in the search for a sperm donor is scarce, even though this search, by isolating a male's genetic impact on offspring from other factors like paternal investment, offers a naturally 'controlled' research setting. In this paper, we work to fill this void by examining the rapidly growing online sperm donor market, which is raising new challenges by offering women novel ways to seek out donor sperm. We not only identify individual factors that influence women's preferences but find strong support for the proposition that inner values are more important in these choices than exterior values. We also find evidence that physical factors matter more than resources or other external cues of material success, perhaps because the relevance of good character in donor selection is part of a female psychological adaptation throughout evolutionary history. The lack of evidence on a preference for material resources, on the other hand, may indicate the ability of socialisation and better access to resources to rapidly shape the female decision process. Overall, the paper makes useful contributions to both the literature on human behaviour and that on decision-making in extreme and highly important situations.
Keywords: J13; D10; Z00; 330; Online sperm donor market; donation recipients preferences; mate choice; sexual selection; evolutionary psychology; internal attributes; exterior attributes